A flexible high thermal conductivity graphene filled polyurethane composite film and preparation method thereof

By uniformly dispersing graphene, carbon quantum dots and one-dimensional film forming agent in polyurethane, forming a strong three-dimensional network structure, the problem of poor thermal conductivity of conventional graphene modified polyurethane thermal conductivity films in the vertical direction is solved, and efficient Thermal conductivity and good mechanical properties.

CN118725542BActive Publication Date: 2025-02-11CHANGZHOU XINDAFANG INNOVATIVE MATERIALS TECH CO LTD

Patent Information

Application Number
CN202410854532.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-02-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The conventional graphene modified polyurethane thermal conductivity has poor thermal conductivity in the vertical direction and cannot meet the application needs.

Method used

The composite film containing thermoplastic polyurethane elastomer, graphene, carbon quantum dots and one-dimensional film forming agent is adopted to realize graphene, carbon quantum dots and film forming agents through processes such as peeling of expanded graphite and high-pressure homogenization. Evenly disperse, forming a strong three-dimensional network structure.

Benefits of technology

The vertical thermal conductivity of the composite film is significantly improved, with the in-plane thermal conductivity up to 50.3W/(m·K), and the vertical thermal conductivity up to 8.7W/(m·K), while improving the tensile strength and fracture strength and density Less than 1.3g/cm3, suitable for the lightweight needs of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725542B_ABST
    Figure CN118725542B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thermally conductive polyester films, and specifically to a flexible high thermal conductivity graphene-filled polyurethane composite film and a preparation method thereof. Conventional graphene-modified polyurethane thermally conductive films have good horizontal thermal conductivity, but poor vertical thermal conductivity. In view of the above problems, the present invention provides a flexible high thermal conductivity graphene-filled polyurethane composite film, wherein the material system contains graphene, carbon quantum dots and a one-dimensional film-forming agent at the same time, and the graphene, carbon quantum dots and the one-dimensional film-forming agent are interconnected, interspersed and stacked to form a complex three-dimensional network structure, and the filler particles are distributed more evenly and densely in the polyurethane resin matrix, which significantly improves the thermal conductivity of the obtained flexible high thermal conductivity graphene-filled polyurethane composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermally conductive polyester films, and in particular to a flexible high-thermal conductive graphene-filled polyurethane composite film and a preparation method thereof. Background Art

[0002] Thermally conductive gaskets are a new type of thermal conductive interface material that has emerged in recent years. They have very low thermal resistance and can be infinitely compressed to fill gaps of various shapes, thereby maximizing the effective area of ​​heat conduction. However, high thermal conductivity gaskets are mainly represented by products from Japanese companies such as Dexerials and Sekisui Chemical. The directional arrangement technology of high thermal conductivity carbon fibers can obtain longitudinal high thermal conductivity gaskets with a thermal conductivity coefficient of up to 15-50W / (m·K). However, the production technology of high thermal conductivity carbon fibers is mainly mastered by a few companies in the United States and Japan. In terms of intellectual property rights, Dexerials and other companies have made in-depth layouts. Domestic companies are still in the catching-up stage in terms of carbon fiber high thermal conductivity gaskets, and it is difficult to make breakthroughs in raw materials, intellectual property rights, etc. in a short period of time.

[0003] Polyurethane is known as the fifth largest plastic. It has outstanding advantages such as light texture, low temperature resistance, aging resistance, and good elasticity. It is widely used in the matrix of thermal interface materials. However, the intrinsic thermal conductivity of polyurethane is low, and thermal conductive fillers such as aluminum oxide, boron nitride, and aluminum nitride are usually added to improve thermal conductivity. The thermal conductivity of graphene is as high as 5300W / (m·K), which is much higher than carbon nanotubes and diamonds. It is the material with the best known thermal conductivity. Secondly, graphene's unique fully soft and thin characteristics give it an extremely low specific gravity, and its density is much lower than mainstream thermal conductive fillers such as aluminum nitride, silicon carbide, aluminum oxide, and zinc oxide. However, graphene has poor dispersibility and compatibility in polyurethane, and is prone to agglomeration in polyurethane, which seriously affects the thermal conductivity, toughness, and tensile strength of polyurethane materials.

[0004] At present, Chinese invention patent CN116694060 A discloses a highly thermally conductive modified polyurethane composite film and its preparation method, which includes the following formula and components: modified graphene, nanosheets, thermoplastic polyurethane, dimethylformamide and catalyst. The patent adds modified graphene and nanosheets to a DMF solution of polyurethane, mixes them evenly, pours them into a polytetrafluoroethylene mold, and flattens them with a glass rod; after drying, a polyurethane thermal conductive composite film is obtained. The preparation technology uses trishydroxymethylaminomethane hydrochloride-modified graphene to improve the dispersibility in DMF and the compatibility with polyurethane, giving the film material excellent thermal conductivity. However, in this technical solution, graphene is prepared by a redox method, and strong oxidants such as sulfuric acid and potassium permanganate are added during the preparation process. The process is complicated and environmentally unfriendly. At the same time, the obtained graphene has many defects and cannot be completely reduced, resulting in residual oxygen-containing groups on the surface that reduce the intrinsic thermal conductivity of graphene. Secondly, the two-dimensional graphene is distributed in parallel in the polyurethane, which only gives the polyurethane film excellent horizontal thermal conductivity, but the thermal conductivity in the vertical direction is poor and cannot meet the application requirements. Summary of the invention

[0005] The problem in the prior art is that conventional graphene-modified polyurethane thermal conductive films have good horizontal thermal conductivity, but poor vertical thermal conductivity. To address the above problem, the present invention provides a flexible high thermal conductivity graphene-filled polyurethane composite film, which comprises the following components by mass ratio:

[0006] Thermoplastic polyurethane elastomer 76-93.9%;

[0007] Graphene 5-20%;

[0008] Carbon quantum dots 1-3%;

[0009] The film-forming agent is 0.1-1%, and the film-forming agent is a one-dimensional tubular or linear structure.

[0010] Preferably, the thermoplastic polyurethane elastomer is a (AB)n type block linear polymer, the A segment is a polyester or polyether with a molecular weight of 1000-6000, and the B segment is a straight chain diol with a carbon chain length of 2-12 carbon atoms.

[0011] Preferably, the graphene has no oxygen-containing functional groups on its structural surface.

[0012] Preferably, the film-forming agent includes one or more of carbon nanotubes, carbon fibers, silicon carbide whiskers, and aluminum nitride whiskers.

[0013] Preferably, the size of the carbon quantum dots is 5-100 nm.

[0014] Preferably, the size of the carbon quantum dots is 5-20 nm.

[0015] Preferably, the preparation method of the flexible high thermal conductivity graphene filled polyurethane composite film comprises the following steps:

[0016] S1: adding expanded graphite, carbon quantum dots and film-forming agent to an organic solvent, dispersing at 500-3000 rpm for 30-60 min to obtain a premix; the mass ratio of carbon quantum dots to expanded graphite is 1:(30-100), the mass ratio of expanded graphite to organic solvent is 1:(20-100), and the mass ratio of film-forming agent to expanded graphite is 1:(100-1000);

[0017] S2: The premix is ​​passed into a sand mill for 6-12 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material. The model of the grinder is wsp-0.5, purchased from Changzhou Longxin Intelligent Equipment Co., Ltd. The operating speed is 500-1000rpm, the feed pressure is ≤0.5MPa, the grinding medium is zirconium beads, the particle size is 2-5mm, and the discharge temperature is ≤60°C;

[0018] S3: The pre-stripped material is passed into a high-pressure homogenizer and further stripped at a pressure of 30-150 MPa to obtain a composite slurry in which graphene, carbon quantum dots and film-forming agent are uniformly dispersed. The high-pressure homogenizer model is GJB500-150, purchased from Changzhou Chaoli Homogenizing Pump Factory, the homogenizing pressure is 30-150 MPa, the homogenizing temperature is ≤60°C, and the time is 30-60 min;

[0019] S4: Add thermoplastic polyurethane elastomer to the composite slurry obtained in S3, disperse it at 500-3000rpm for 10-60min to fully dissolve the thermoplastic polyurethane elastomer, and then apply it to the surface of the substrate. After drying, peel it off from the surface of the substrate to obtain a flexible high thermal conductivity graphene filled polyurethane composite film, wherein the mass ratio of the thermoplastic polyurethane elastomer to the expanded graphite in the composite slurry is (15-20):1.

[0020] Preferably, the mass ratio of carbon quantum dots to expanded graphite is 1:(50-100).

[0021] Preferably, the mass ratio of the film-forming agent to the expanded graphite is 1:(200-1000).

[0022] Preferably, a dispersant is further added to S1, and the dispersant includes one or more of polyethylene glycol, polyvinyl pyrrolidone, and polysorbate 80.

[0023] Preferably, the mass ratio of the dispersant to the expanded graphite is 1:(50-200)

[0024] Preferably, the mass ratio of the dispersant to the expanded graphite is 1:(100-200).

[0025] Preferably, the coating thickness in S4 is 200-5000 μm.

[0026] Preferably, the drying temperature in S4 is 50-80°C.

[0027] The present invention has the following beneficial effects:

[0028] (1) The flexible high thermal conductivity graphene-filled polyurethane composite film obtained by the present invention contains graphene, carbon quantum dots and a one-dimensional film-forming agent at the same time, wherein the one-dimensional film-forming agent is at least one of carbon nanotubes, carbon fibers, silicon carbide whiskers and aluminum nitride whiskers. In the process of obtaining graphene by exfoliating expanded graphite, the carbon quantum dots in the formulation system are subjected to grinding and homogenization, and can be more evenly adsorbed on the surface of the exfoliated graphene, which significantly improves the reversible agglomeration phenomenon of the graphene in the subsequent processing process, is conducive to further improving the uniform dispersion of graphene in the thermoplastic polyurethane elastomer, and is very beneficial to improving the thermal conductivity of the obtained composite film;

[0029] (2) Carbon quantum dots can effectively fill the gaps formed between graphene and the one-dimensional film-forming agent, further improving the thermal conductivity of the composite film in the vertical direction;

[0030] (3) The one-dimensional film-forming agent, zero-dimensional carbon quantum dots and graphene form a strong three-dimensional network structure, which can further improve the film-forming property of the obtained composite film and significantly improve the tensile strength and breaking strength of the obtained composite film;

[0031] (4) The one-dimensional film-forming agent also has a high theoretical thermal conductivity, which can improve the thermal conductivity of the composite film in the vertical direction and further reduce the interfacial thermal resistance. The obtained flexible high thermal conductivity graphene filled polyurethane composite film has an in-plane thermal conductivity of up to 50.3 W / (m·K) and a vertical thermal conductivity of 8.7 W / (m·K);

[0032] (5) The thermal conductive filler and film-forming agent used in the present invention are both carbon materials, both of which have a relatively low mass density. The density of the obtained composite film is only 1.1-1.3 g / cm 3 , which can meet the demand for lightweight electronic devices;

[0033] (6) The flexible high thermal conductivity graphene-filled polyurethane composite film obtained in the present invention overcomes the key problems of conventional graphene-modified polyurethane films, and the preparation process is simpler and more efficient, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 : Bending effect diagram of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 1 of the present invention.

[0035] Figure 2 : Schematic diagram of the spiral winding effect of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0037] The carbon quantum dots used in the following examples of the present invention were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with a product number of 104848.

[0038] The expanded graphite used in the following examples of the present invention was purchased from Qingdao Yanhai Carbon Material Co., Ltd. and the brand is YH-100.

[0039] The carbon nanotubes used in the following examples of the present invention were purchased from Jiangsu Tiannai Technology Co., Ltd. with the item number LB107-44.

[0040] The carbon fiber used in the following examples of the present invention was purchased from Showa Denko K.K. of Japan and its brand number is VGCF-H.

[0041] The silicon carbide whiskers used in the following examples of the present invention were purchased from Aladdin Chemical Reagent Network with the item number S196604.

[0042] The aluminum nitride whiskers used in the following examples of the present invention were purchased from Aladdin Chemical Reagent Network with a product number of A109772.

[0043] The thermoplastic polyurethane elastomer used in the following examples of the present invention is purchased from BASF, Germany, and its brand number is 1185A.

[0044] The process parameters of sand mill grinding in the following embodiments of the present invention are as follows:

[0045] The grinder model is wsp-0.5, the manufacturer is Changzhou Longxin Intelligent Equipment Co., Ltd., the operating speed is 1000rpm, the feed pressure is 0.5MPa, the grinding medium is zirconium beads, the particle size is 2mm, and the discharge temperature is 60℃.

[0046] The process parameters of the high pressure homogenizer in the following embodiments of the present invention are as follows:

[0047] The homogenization pressure is 150 MPa, the homogenization temperature is 60°C, and the time is 30 min.

[0048] The mRGO in Comparative Example 4 was prepared according to the method described in Example 1 of Chinese invention patent CN116694060A.

[0049] Example 1

[0050] (1) 5 g of expanded graphite, 0.16 g of carbon quantum dots, 0.05 g of carbon nanotubes and 0.025 g of polyethylene glycol (molecular weight 4000) were weighed and added into 100 g of N-methylpyrrolidone, and dispersed at 500 rpm for 60 min to obtain a premix, wherein the average particle size of the carbon nanotubes was 100 nm;

[0051] (2) passing the premix into a sand mill and sand grinding for 6 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material;

[0052] (3) passing the pre-stripped material into a high-pressure homogenizer and homogenizing it once at a pressure of 150 MPa to obtain a composite slurry in which graphene, carbon quantum dots and carbon nanotubes are uniformly dispersed;

[0053] (4) Weigh 94.9 g of thermoplastic polyurethane elastomer and add it to the above composite slurry, stir and disperse at 3000 rpm until the thermoplastic polyurethane elastomer is completely dissolved to form a uniform mixed slurry, and then apply the mixed slurry on the surface of the glass substrate to form a film with a coating thickness of 500 μm. Thereafter, dry it at 50° C. to obtain a flexible high thermal conductivity graphene-filled polyurethane composite film.

[0054] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 1 is 30.2 W / (m·K), the vertical thermal conductivity is 3.9 W / (m·K), and the density is 1.1 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0055] The flexibility of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 1 is as follows: Figure 1 and Figure 2 As shown, after folding and spiral winding, the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 1 is still intact without any cracks.

[0056] Example 2

[0057] (1) 5 g of expanded graphite, 0.16 g of carbon quantum dots, 0.05 g of silicon carbide whiskers and 0.1 g of polyethylene glycol (molecular weight 4000) were weighed and added to 100 g of N-methylpyrrolidone, and dispersed at 3000 rpm for 30 min to obtain a premix, wherein the average particle size of the carbon nanotubes was 20 nm;

[0058] (2) passing the premix into a sand mill and sand grinding for 12 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material;

[0059] (3) passing the pre-stripped material into a high-pressure homogenizer and homogenizing it twice at a pressure of 120 MPa to obtain a composite slurry in which graphene, carbon quantum dots and silicon carbide whiskers are uniformly dispersed;

[0060] (4) Weigh 94 g of thermoplastic polyurethane elastomer and add it to the above composite slurry, stir and disperse at 2000 rpm until the thermoplastic polyurethane elastomer is completely dissolved to obtain a uniform mixed slurry, and then apply the mixed slurry on the surface of a glass substrate to form a film with a coating thickness of 500 μm, and dry it at 80° C. to obtain a flexible high thermal conductivity graphene-filled polyurethane composite film.

[0061] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 2 is 33.6 W / (m·K), the vertical thermal conductivity is 3.5 W / (m·K), and the density is 1.2 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0062] Example 3

[0063] (1) Weigh 20 g of expanded graphite, 0.5 g of carbon quantum dots, 0.02 g of aluminum nitride whiskers and 0.4 g of polyvinyl pyrrolidone (molecular weight 8000) and add them to 1000 g of N-methyl pyrrolidone, and disperse them at 2000 rpm for 50 min to obtain a premix. The average particle size of the carbon quantum dots is 5 nm.

[0064] (2) passing the premix into a sand mill and sand grinding for 12 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material;

[0065] (3) passing the pre-stripped material into a high-pressure homogenizer and homogenizing it three times at a pressure of 80 MPa to obtain a composite slurry in which graphene, carbon quantum dots and aluminum nitride whiskers are uniformly dispersed;

[0066] (4) Weigh 300 g of thermoplastic polyurethane elastomer and add it to the above composite slurry, stir and disperse at 500 rpm until the polyurethane is completely dissolved to obtain a uniform mixed slurry, and then apply the mixed slurry on the surface of a glass substrate to form a film with a coating thickness of 1000 μm. Dry at 60° C. to obtain a flexible high thermal conductivity graphene-filled polyurethane composite film.

[0067] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 3 is 50.3 W / (m·K), the vertical thermal conductivity is 8.7 W / (m·K), and the density is 1.3 g / cm 3The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0068] Example 4

[0069] (1) 10 g of expanded graphite, 0.2 g of carbon quantum dots, 0.1 g of carbon fiber and 0.05 g of polyvinyl pyrrolidone (molecular weight 8000) were weighed and added to 200 g of N-methyl pyrrolidone, and dispersed at 3000 rpm for 30 min to obtain a premix, wherein the average particle size of the carbon quantum dots was 10 nm;

[0070] (2) passing the premix into a sand mill and sand grinding for 8 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material;

[0071] (3) passing the pre-stripped material into a high-pressure homogenizer and homogenizing it 8 times at a pressure of 30 MPa to obtain a composite slurry in which graphene, carbon quantum dots and carbon fibers are uniformly dispersed;

[0072] (4) Weigh 150 g of thermoplastic polyurethane elastomer and add it to the above-mentioned composite slurry, stir and disperse at 1000 rpm until the thermoplastic polyurethane elastomer is completely dissolved to obtain a uniform mixed slurry, and then apply the slurry on the surface of a glass substrate to form a film with a coating thickness of 1000 μm. Thereafter, dry it at 70°C to obtain a flexible and highly thermally conductive graphene-filled polyurethane composite film.

[0073] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 4 is 38.1 W / (m·K), the vertical thermal conductivity is 5.3 W / (m·K), and the density is 1.1 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0074] Example 5

[0075] (1) 10 g of expanded graphite, 0.2 g of carbon quantum dots, 0.1 g of carbon nanotubes and 0.2 g of polysorbate 80 were weighed and added to 200 g of N-methylpyrrolidone, and dispersed at 2000 rpm for 40 min to obtain a premix, wherein the average particle size of the carbon quantum dots was 80 nm;

[0076] (2) passing the premix into a sand mill and sand grinding for 10 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material;

[0077] (3) passing the pre-stripped material into a high-pressure homogenizer and homogenizing it 5 times at a pressure of 60 MPa to obtain a composite slurry in which graphene, carbon quantum dots and carbon nanotubes are uniformly dispersed;

[0078] (4) Weigh 150 g of thermoplastic polyurethane elastomer and add it to the above composite slurry, stir and disperse at 3000 rpm until the thermoplastic polyurethane elastomer is completely dissolved to obtain a uniform mixed slurry, and then apply the slurry on the surface of a glass substrate to form a film with a coating thickness of 3000 μm. Dry at 60° C. to obtain a flexible high thermal conductivity graphene-filled polyurethane composite film.

[0079] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Example 5 is 41.5 W / (m·K), the vertical thermal conductivity is 6.8 W / (m·K), and the density is 1.1 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0080] Comparative Example 1 is the same as Example 5, except that carbon nanotubes and carbon quantum dots are not added in step (1) of Comparative Example 1.

[0081] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Comparative Example 1 is 20.6W / (m·K), the vertical thermal conductivity is 0.9W / (m·K), and the density is 1.1g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0082] Comparative Example 2 is the same as Example 5, except that no carbon nanotubes are added in step (1) of Comparative Example 2, and the amount of carbon quantum dots added is 0.3 g.

[0083] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Comparative Example 2 is 26.4W / (m·K), the vertical thermal conductivity is 2.1W / (m·K), and the density is 1.2g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0084] Comparative Example 3 is the same as Example 5, except that in step (1) of Comparative Example 3, no carbon quantum dots are added, and the amount of carbon nanotubes added is 0.3 g.

[0085] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Comparative Example 3 is 28.5 W / (m·K), the vertical thermal conductivity is 2.5 W / (m·K), and the density is 1.2 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0086] Comparative Example 4 is the same as Example 5, except that the polyurethane composite film in Comparative Example 4 is prepared according to the following steps:

[0087] (1) 10 g mRGO, 0.2 g carbon quantum dots, 0.1 g carbon nanotubes and 0.2 g polysorbate 80 were weighed and added into 200 g N-methylpyrrolidone, and dispersed at 2000 rpm for 40 min to obtain a premix, wherein the average particle size of the carbon quantum dots was 80 nm, and the graphene oxide was graphene oxide prepared by Hummer's method;

[0088] (2) Weigh 150 g of thermoplastic polyurethane elastomer and add it to the above premix, stir and disperse at 3000 rpm until the thermoplastic polyurethane elastomer is completely dissolved to obtain a uniform mixed slurry, then apply the slurry on the surface of the substrate to form a film with a coating thickness of 3000 μm, and dry it at 60° C. to obtain a flexible high thermal conductivity graphene-filled polyurethane composite film.

[0089] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Comparative Example 4 is 29.8W / (m·K), the vertical thermal conductivity is 2.8W / (m·K), and the density is 1.3g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0090] Comparative Example 5 is the same as Example 5, except that the expanded graphite (Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., brand 7782-42-5) used in Comparative Example 5 has oxygen-containing functional groups.

[0091] The test shows that the in-plane thermal conductivity of the flexible high thermal conductivity graphene filled polyurethane composite film obtained in Comparative Example 5 is 29.5 W / (m·K), the vertical thermal conductivity is 3.0 W / (m·K), and the density is 1.3 g / cm 3 The in-plane thermal conductivity test adopts the laser method (test standard ASTM E1461), and the vertical thermal conductivity test adopts the steady-state heat flow method (test standard ASTMD5470).

[0092] The test performance data of the flexible high thermal conductivity graphene-filled polyurethane composite films obtained in Examples 1-5 of the present invention and Comparative Examples 1-5 are summarized in Table 1 and Table 1.

[0093] Table 1

[0094] Test items In-plane thermal conductivity W / (m·K) Vertical thermal conductivity W / (m·K) Example 1 30.2 3.9 Example 2 33.6 3.5 Example 3 50.3 8.7

[0095] Table 1

[0096] Test items In-plane thermal conductivity W / (m·K) Vertical thermal conductivity W / (m·K) <![CDATA[Density g / cm 3 > Example 4 38.1 5.3 1.1 Example 5 41.5 6.8 1.1 Comparative Example 1 20.6 0.9 1.1 Comparative Example 2 26.4 2.1 1.2 Comparative Example 3 28.5 2.5 1.2 Comparative Example 4 29.8 2.8 1.3 Comparative Example 5 29.5 3.0 1.3

[0097] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A flexible high thermal conductivity graphene filled polyurethane composite film, characterized in that: In terms of mass ratio, it contains the following ingredients: Thermoplastic polyurethane elastomer 76-93.9%; Graphene 5-20%; Carbon quantum dots 1-3%; 0.1-1% of film-forming agent, wherein the film-forming agent is a one-dimensional tubular or linear structure; The method for preparing the flexible high thermal conductivity graphene filled polyurethane composite film comprises the following steps: S1: Add expanded graphite, carbon quantum dots and film-forming agent into an organic solvent, and disperse them at 500-3000 rpm for 30-60 min to obtain a premix; the mass ratio of carbon quantum dots to expanded graphite is 1:(30-100), the mass ratio of expanded graphite to organic solvent is 1:(20-100), and the mass ratio of film-forming agent to expanded graphite is 1:(100-1000); S2: The premix is ​​passed into a sand mill and sand-milled for 6-12 hours to exfoliate the expanded graphite to obtain a pre-exfoliated material. The operating speed is 500-1000rpm, the feed pressure is ≤0.5MPa, the grinding medium is zirconium beads, the particle size is 2-5 mm, and the discharge temperature is ≤60°C; S3: The pre-stripped material is passed into a high-pressure homogenizer and further stripped at a pressure of 30-150 MPa to obtain a composite slurry in which graphene, carbon quantum dots and film-forming agent are uniformly dispersed. The homogenization pressure is 30-150 MPa, the homogenization temperature is ≤60°C, and the time is 30-60 min; S4: adding a thermoplastic polyurethane elastomer to the composite slurry obtained in S3, dispersing at 500-3000 rpm for 10-60 min to fully dissolve the thermoplastic polyurethane elastomer, and then coating it on the surface of the substrate, and peeling it off from the surface of the substrate after drying to obtain a flexible high thermal conductivity graphene filled polyurethane composite film, wherein the mass ratio of the thermoplastic polyurethane elastomer to the expanded graphite in the composite slurry is (15-20):1; The expanded graphite does not contain oxygen-containing functional groups; The film-forming agent includes one or more of carbon nanotubes, carbon fibers, silicon carbide whiskers, and aluminum nitride whiskers.

2. A flexible high thermal conductivity graphene filled polyurethane composite film according to claim 1, characterized in that: Thermoplastic polyurethane elastomer is a (AB)n type block linear polymer, wherein the A segment is a polyester or polyether with a molecular weight of 1000-6000, and the B segment is a straight-chain diol with a carbon chain length of 2-12 carbon atoms.

3. A flexible high thermal conductivity graphene filled polyurethane composite film according to claim 1, characterized in that: The size of the carbon quantum dots is 5-100 nm.

4. A flexible high thermal conductivity graphene filled polyurethane composite film according to claim 3, characterized in that: The size of the carbon quantum dots is 5-20 nm.

5. The preparation method according to claim 1, characterized in that: A dispersant is also added to S1, and the mass ratio of the dispersant to the expanded graphite is 1:(50-200).

6. The preparation method according to claim 5, characterized in that: The mass ratio of the dispersant to the expanded graphite is 1:(100-200).

7. The preparation method according to claim 1, characterized in that: The coating thickness in S4 is 200-5000 μm.

Citation Information

Patent Citations

  • High-thermal-conductivity modified polyurethane composite film and preparation method thereof

    CN116694060A

  • Graphene contained flexible film and preparation method thereof

    CN108495385A

  • Preparation method of CDs / TPU fluorescent nanocomposite

    CN109504368A

Cited By

  • High-thermal-conductivity graphene composite film for electronic component and preparation method of high-thermal-conductivity graphene composite film

    CN122103864A